Simazine Enhances Dark Fermentative H2 Production by Unicellular Halotolerant Cyanobacterium Aphanothece halophytica - Pansook, Sunisa; Incharoensakdi, Aran; Phunpruch, Saranya (Frontiers in Bioengineering and Biotechnology, 2022)
The halotolerant cyanobacterium Aphanothece halophytica is a potential H2 producer that induces H2 evolution under nitrogen deprivation. H2 is mainly produced via a catabolism of storage glycogen under dark anaerobic condition. H2 evolution is catalyzed by O2-sensitive bidirectional hydrogenase. The aim of this study was to improve H2 production by A. halophytica using various kinds of inhibitors. Among all types of inhibitors, simazine efficiently promoted highest H2 production under dark condition. High simazine concentration and long-term incubation resulted in a decrease in cell and chlorophyll concentrations. The optimal simazine concentration for H2 production by A. halophytica was 25 µM. Simazine inhibited photosynthetic O2 evolution but promoted dark respiration, resulting in a decrease in O2 level. Hence, the bidirectional hydrogenase activity and H2 production was increased. A. halophytica gave the highest H2 production rate at 58.88 ± 0.22 µmol H2 g-1 dry weight h-1 and H2 accumulation at 356.21 ± 6.04 μmol H2 g-1 dry weight after treatment with 25 µM simazine under dark anaerobic condition for 2 h and 24 h, respectively. This study demonstrates the potential of simazine for the enhancement of dark fermentative H2 production by A. halophytica.